Role of MSME in Absorbing Labor and Contribution to GDP - Muhammad Suhaili; Sugiharsono Sugiharsono (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
The purpose of this study is to analyze the role of MSMEs in absorbing labor and its contribution to GDP in Indonesia. The type of data used is secondary data from the Central Statistics Agency (BPS) and the Ministry of Cooperatives and MSMEs. The analytical method used is descriptive statistics. The results showed that the average number of UMKM labor was 112,709,244 or 97.03%. Micro-businesses absorbed 92% of the workforce, 5% of small businesses and medium-sized businesses were 3% of the total MSMEs workforce. The average contribution of MSMEs to Indonesia's GDP during the 2012-2017 period was Rp.5,928,934.98 billion or 59.74%. Micro-enterprises contributed the most, 61.05%, small- enterprises 16.20% and medium- enterprises at 22.75% of the total GDP of MSMEs.